Changes in the antibiotic-resistant properties of pathogenic microorganisms in patients with purulent-necrotic wounds against the background of type 2 diabetes when using a probiotic antiseptic - Ioffe, O. Y.; Stetsenko, O. P.; Kindzer, S. L.; Kryvopustov, M. S.; Tsyura, Y. P.; Prykhodko, Y. S. (General Surgery, 2024)
Antibiotic resistance remains a serious problem, leading to millions of deaths every year. The increasing prevalence of type 2 diabetes mellitus (T2DM) is contributing to the continued spread of this problem. Ukraine, like other countries, feels the consequences of this problem. Over the past ten years, the number of patients with T2DM has doubled, and diabetes is already the cause of disability and death for thousands of people. Complications of T2DM, such as diabetic foot syndrome, often require surgery and antibacterial therapy. New research shows the prospects of using probiotic antiseptics based on lactic acid bacteria of the genus Bacillus in the treatment of wounds, which may open new opportunities to combat this problem and improve treatment outcomes. Objective — to analyse changes in the antibiotic‑resistant properties of pathogenic microorganisms in patients with purulent‑necrotic wounds in type 2 diabetes mellitus. Materials and methods. The study, which was conducted at the Department of General Surgery No. 2 of Bogomolets National Medical University in Kyiv City Clinical Hospital No. 3, included 229 patients with purulent‑necrotic wounds and type II diabetes. A total of 229 patients were randomly divided into two groups, with one group receiving probiotic antiseptics and the other traditional chemical antiseptics, with subsequent analysis focusing on changes in antibiotic‑resistant properties against P. aeruginosa and K. pneumoniae. Antibiotic‑resistant properties were evaluated through microbiological examination, revealing significant changes in resistance patterns among patients treated with probiotic antiseptics compared to those using traditional chemical antiseptics, assessed using statistical methods including the Student’s t‑test and Wilcoxon W‑test. Results. When the first subgroups were compared on the first day, there was no statistically significant difference in the levels of P. aeruginosa wound contamination (p=0.671). On the seventh day, there was a statistically significant difference between contamination levels (p<0.05) and the emergence of sensitivity to reserve antibiotics (p<0.05). On the 14th day, there was a statistically significant difference between contamination levels (p<0.05) and the emergence of sensitivity to reserve antibiotics (p<0.05). Conclusions. Probiotic antiseptics have a statistically significant advantage over chemical antiseptics in terms of reducing contamination and emergence of antibiotic sensitivity in patients with purulent‑necrotic wounds in type 2 diabetes mellitus.